Analisis Komparatif Terhadap Penguasaan Ragam Kata dan Kompleksitas Tuturan pada Anak Usia 7 dan 9 Tahun: Kajian Psikolinguistik - Adam, Marsadi; Muslima, Nasywah Hanifa; Putra, Dona Aji Karunia (GERAM (Gerakan Aktif Menulis), 2025)
This study is based on the theory of language acquisition, which suggests that language is the result of the interaction between cognitive development and the social environment, referring to the cognitive theories of Piaget and Vygotsky and combined with syntactic theory. This study used a qualitative approach with a descriptive design. The research findings show that both subjects are able to produce logically structured and coherent speech, but the level of sentence complexity used varies at each age. Seven-year-old children used more simple and compound sentences, while nine-year-old children showed a tendency to produce compound and compound-complex utterances with a more varied number of clauses, and seven-year-old children produced more simple sentences than nine-year-old children, who did not produce simple sentences at all. These differences illustrate that age, cognitive maturity, and the intensity of social interaction significantly influence children's language abilities, particularly regarding vocabulary variety and syntactic complexity. These findings align with Piaget's and Vygotsky's theories, which emphasize that language develops through a combination of cognitive processes and the social environment.